Content Management - APQC's Passport to Success Series A Guide for Your Journey to Knowledge Management Best Practices - Hasanali, Farida; Hasanali, Farida; Leavitt, Paige (APQC American Productivity & Quality Center, 2003)
Content Management: A Guide for Your Journey to Knowledge Management Best Practices details steps to fully incorporate a content management system into regular operations. JUSTIFY A CONTENT MANAGEMENT SYSTEM - Identify a strategic rationale for investing in a content management system and estimate costs. PLAN AND DESIGN - Analyze needs and support structures. Create a taxonomy and operations process. Audit content and assess vendors. IMPLEMENT THE SYSTEM - Deploy the plan for content management implementation and support the established players. MAINTAIN AND UPGRADE - Monitor the evolution of processes, technology, and roles over time. Chapters are also included concerning the lifecycles of content, information technology, and lessons learned. Best-practice examples from leading organizations are summarized to illustrate findings.